2018
DOI: 10.18502/kls.v4i5.2573
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention, Driving Behavior and Driving Performance among Young Drivers in Sleep-deprived Condition

Abstract: Traffic accident is one of the main causes of death among young drivers, both in developed and developing country. Sleep deprivation is agreed to be one of the major contributing factors. In this study, we investigate the effect of sleep deprivation on visual attention during driving and how it contributes to driving behaviors and performance. Twelve male students (mean age = 21.6 years, SD = 0.6 years) who already had valid driving license participated in this study. They were required to drive on a driving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The sleepy and fatigued drivers had small variations of speed, as reported in [35]. However, the speed was higher in the sleep deprived groups, as compared to the normal sleep group [36].…”
Section: Driver's Performance Evaluationmentioning
confidence: 65%
See 2 more Smart Citations
“…The sleepy and fatigued drivers had small variations of speed, as reported in [35]. However, the speed was higher in the sleep deprived groups, as compared to the normal sleep group [36].…”
Section: Driver's Performance Evaluationmentioning
confidence: 65%
“…From the driving simulator, the performances are evaluated based on two types of measurements: vehicle and road-based; and, driver's physical and behavior-based. The vehicle and road-based measurements were analyzed in the perspective of lane deviation [32]- [35], speed maintenance [35], [36], car-following distance [35], and crash occurrences [33]. The sleepy and fatigued drivers had small variations of speed, as reported in [35].…”
Section: Driver's Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive load could affect driving negatively, undermining drivers’ driving performance (Lee et al, 2007; Wijayanto et al, 2018). The increased cognitive load was associated with a common network comprising occipital cortices and parietal, thalamus, and the cerebellum (Tomasi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among these areas, the occipital and parietal cortex are crucial in visual spatial attention functioning (Garg et al, 2007; Weaver and Stevens, 2007; Lauritzen et al, 2009). Visual spatial attention is a kind of attention, including a series of cognitive activities, such as visual searching, spatial area selection, attention switching and selective visual information processing in the useful field of view (Richardson and Marottoli, 2003; Wijayanto et al, 2018). Researches indicated that visual attention played an important role in predicting driving task performance, which is associated with a threefold increase in the risk of driving errors (Richardson and Marottoli, 2003).…”
Section: Discussionmentioning
confidence: 99%